ANALISIS ARGUMENTASI PESERTA DIDIK KELAS X SMA MUHAMMADIYAH 1 PALEMBANG DENGAN MENGGUNAKAN MODEL ARGUMENTASI TOULMIN - Putri Handayani (Universitas Sriwijaya, 2015)
The study aimed to analyze argumentation of students in senior high school the first grade in Muhammadiyah 1 Palembang about Elastisitas and Hook Law’s Subject with the Argumentation Skill Through Toulmin. Theory Argumentation Toulmin is intruments the data’s collect for analyze the student’s argumentation. Data, Claim, Warrant, Backing, Qualifier, and Rebutal are component parts of Theory Argumentation Toulmin.The Result of analyze about student’s argumenatation Data 92 % student that know the information they have, the fact or evidence used to prove the argument, Claim 92% Student can write their opinion as their argumentation, the statement being argue. Warrant 81% the general, hypothetical logical statement that serve as bridges between the Claim and Data, 74% Backing, Statements that serve to support the warrants, prove the main point being argued, but which do prove the warrants are true , 38% Qualifiers, Statements taht limit the strength of asrguments or statements that purpose the conditions under which the arguments is true. and the lastRebuttals 93% Conter-arguments or statements indicating circumstance when the general argument does not hold true.